2012
DOI: 10.1007/s00210-012-0784-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypercholesterolemia on carbachol-induced contractions of the detrusor smooth muscle in rats: increased role of L-type Ca2+ channels

Abstract: To investigate a possible relation between hypercholesterolemia and detrusor smooth muscle function, we studied the contractile response to potassium challenge, carbachol (CCh), and the components of CCh-induced contractile mechanism in high-cholesterol diet-fed rats. Adult male Sprague-Dawley rats were fed with standard (control group, N = 17) or 4 % cholesterol diet (hypercholesterolemia group (HC), N = 16) for 4 weeks. Spontaneous contractions of detrusor muscle strips and their responses to potassium chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…To determine mechanisms underlying the increased pressor and vascular tone, we focused on resistance arteries and ion channels on smooth muscle cells. Numerous studies showed physiopathologic basis of vascular disorders involving dysfunction of L-type Ca 2+ channels, e.g, an up-regulation of LTCCs in the genesis of hypertension and hypercholesterolemia 36 38 39 . Recently, our colleagues demonstrated that high-sucrose diets in pregnancy altered angiotensin II-mediated pressor responses and vessel tone via PKC/Cav1.2 pathway 40 .…”
Section: Discussionmentioning
confidence: 99%
“…To determine mechanisms underlying the increased pressor and vascular tone, we focused on resistance arteries and ion channels on smooth muscle cells. Numerous studies showed physiopathologic basis of vascular disorders involving dysfunction of L-type Ca 2+ channels, e.g, an up-regulation of LTCCs in the genesis of hypertension and hypercholesterolemia 36 38 39 . Recently, our colleagues demonstrated that high-sucrose diets in pregnancy altered angiotensin II-mediated pressor responses and vessel tone via PKC/Cav1.2 pathway 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Twelve male SpragueDawley rats of 4-7 weeks old were divided into control (n = 6) and cholesterol (n = 6) groups. The control group (NC) was fed with standard rat chow and the cholesterol group (HC) was fed with a high cholesterol diet (4% cholesterol and 0.2% deoxycholate) for 4 weeks (22,23). All rats were kept in standard conditions (room temperature in a 12-h light/12-h dark cycle) with free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…High-cholesterol diet-induced hypercholesterolemia is widely used for studies on monkeys [42], hamsters [43], guinea pigs [44], rabbits [20,27,29,45,46], rats [19,[47][48][49] and mice [50]. The dietary-induced hypercholesterolemia model has several advantages.…”
Section: High-cholesterol Diet Modelmentioning
confidence: 99%